STRATEGI PEMASARAN PT. MITRAGAMA INTIPERKASA UNTUK MENINGKATKAN PENJUALAN UNIT RUMAH LA PALMA GRANDE BEKASI - Ahmad Zita; Venny Oktaviany (Institut Bisnis Muhammadiyah Bekasi, 2023)
This research studies marketing strategies for the increase of house sales at La Palma Grande, PT. Mitragama Intiperkasa according to product, location, price, and promotion with several observations and interviews with related parties. The type of research was qualitative descriptive by selecting some information sourced and direct observation of the location. The result of this research states the product, location, price, and promotion La Palma Grande greatly affect the increase in sales. The result of the observation of the location of La Palma Grande is very strategic, residential locations directly access the main road, near the highway, education facilities, health facilities and hospital, shopping center, industrial area, business, and office areas as well as tourist attractions. In terms of price, the results of interview respondents in La Palma Grande are very affordable for factory employees, civil servants, state-owned enterprises, entrepreneurs, and private employees, starting price from 400 million in 2022.